Pharmacokinetics and nephrotoxicity of cisplatin modulated by combination therapy with brusatol - Guo, Nan; Zhang, Yahui; Yuan, Guiyan; Zhang, Xiaoran; Zhang, Wen; Wen, Qing (Frontiers in Pharmacology, 2026)
Ethnopharmacological RelevanceQuassinoid brusatol, isolated from the traditional Chinese medicine Brucea javanica (L.) Merr., significantly increases the intracellular concentration of cisplatin and reduces tumor size by inhibiting the Nrf2 pathway. However, the underlying mechanism remains unclear.ObjectiveThis study focuses on the effects of brusatol on plasma pharmacokinetics, tissue distribution, and nephrotoxicity of cisplatin.Materials and MethodsFor the pharmacokinetic study, 120 Kunming mice were randomly assigned to receive cisplatin (10 mg/kg) alone or in combination with brusatol (2 mg/kg). Blood and tissue samples were collected to evaluate the in vivo pharmacokinetic interaction. In the nephrotoxicity study, 30 Kunming mice were randomly divided into groups to receive cisplatin (10 mg/kg) alone or brusatol pretreatment (1 mg/kg or 2 mg/kg). Two control groups received brusatol (1 mg/kg) or solvent. Blood samples and kidney tissues were collected to investigate the underlying mechanisms of toxicity.ResultsThe developed HPLC-MS method demonstrated high precision and accuracy, meeting the requirements for biological sample analysis. Brusatol reduced the plasma concentration of cisplatin, increased the apparent volume of distribution (Vd), and significantly increased cisplatin concentrations in the kidney and lung, particularly in the kidney. Combined with brusatol, serum levels of blood urea nitrogen and creatinine increased, antioxidant indices in kidney tissue decreased, and inflammatory factors increased. Pathological findings revealed increased tubular congestion.Discussion and ConclusionBrusatol increases renal cisplatin concentrations by altering its pharmacokinetics, intensifying dose-dependent nephrotoxicity. Further development as a chemotherapy sensitizer requires understanding the mechanisms of this effect and optimizing the combined dose.